1994
DOI: 10.1002/pen.760342408
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial tension in polymer melts. Part II: Effects of temperature and molecular weight on interfacial tension

Abstract: Interfacial tension is one of the most important parameters that govern the morphology of polymer blends and the quality of adhesion between polymers. However, few data are available on interfacial tension due to experimental difficulties. A pendant drop apparatus was used for the determination of the interfacial tension for the polymer pair polypropylene/polystyrene (PP/PS). The effects of temperature and molecular weight were evaluated. The range of temperatures used was from 178° to 250°C, and the range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
40
0
4

Year Published

1995
1995
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 15 publications
8
40
0
4
Order By: Relevance
“…This is understood from the fact that mixing of long molecules is less favorable, 13 a well known phenomenon that was reported earlier. 33,34 The results also show that the effect of the low molecular weight phase ͑here this is always the drop phase except for the B3 combination͒ on the value of the interfacial tension ͑the A combinations versus the B combinations͒ is more pronounced than the ratio of the molecular weight. For example, the systems B4 and A3 have the same order of asymmetry but a large difference in the interfacial tension ␥ while the systems B3 and B4 have a big difference in asymmetry but relatively small difference in ␥.…”
Section: A Transient Interfacial Tension and Drop Size Reductionsupporting
confidence: 48%
“…This is understood from the fact that mixing of long molecules is less favorable, 13 a well known phenomenon that was reported earlier. 33,34 The results also show that the effect of the low molecular weight phase ͑here this is always the drop phase except for the B3 combination͒ on the value of the interfacial tension ͑the A combinations versus the B combinations͒ is more pronounced than the ratio of the molecular weight. For example, the systems B4 and A3 have the same order of asymmetry but a large difference in the interfacial tension ␥ while the systems B3 and B4 have a big difference in asymmetry but relatively small difference in ␥.…”
Section: A Transient Interfacial Tension and Drop Size Reductionsupporting
confidence: 48%
“…In addition, the experimental values stay between the harmonic Table 5 that the change in (-dg/dT) from 0.06 to 0.08 does not change significantly the calculated interfacial tension values. For the PBT/SAN system, it was observed an increase in the interfacial tension as a function of the increase in the PBT molecular weight, as already observed by Kamal 25 for PP/ PS systems. For that system the increase was observed up to a certain molecular weight then it leveled off for further increase.…”
Section: Resultssupporting
confidence: 80%
“…The most easily accessible thermodynamic parameter related to the interfacial zone, that also controls morphology and adhesion properties in polymer blends, is interfacial tension and therefore, the focus is to study its evolution in time. In Peters et al [10] it is concluded that increasing the molecular weight of either phase, matrix or drop, leads to higher values of the interfacial tension, in accordance with the results shown in [1,[11][12][13], and it is reported that, above a critical molecular weight value, a plateau value in interfacial tension is approached. The influence of temperature is studied in [1,11,[13][14][15] and both an increase and Wagner et al [14] even found a maximum in σ (t) for some combinations of chains lengths, attributed to close miscibility gaps.…”
Section: Introductionsupporting
confidence: 75%